Negotiation of meaning in l2 vocabulary acquisition in synchronous computer-mediated and face-to-face contexts / Cheah Kah Mun - Cheah, Kah Mun (2016)
Learning the vocabulary of a language is one of the essential components of learning of a second language (L2). In a language classroom, time factor prompts most of the teachers to conduct explicit vocabulary teaching which requires the learners to memorise a large amount of vocabulary (Alemi, Sarab & Lari, 2012). But, according to Cervatiuc (2008), although the students try to recite the new vocabulary repeatedly, it is impossible to memorise a large amount of vocabulary. Thus, the negotiation of meaning is recognised as a good alternative method in learning vocabulary (Smith, 2003; Varonis and Gass, 1985). The mixed-method design (Creswell, 2014) in this study utilises the quantitative method to investigate the effectiveness of synchronous computer-mediated and face-to-face interactions in English vocabulary acquisition, whilst the qualitative method is used to explore the nature of negotiation of meaning in this study. The pretest, immediate and delayed post-tests were administered to 8 synchronous computermediated dyads and 8 face-to-face dyads of participants. The dyads negotiated in Facebook or face-to-face to complete information gap tasks. The results of the post-tests indicated that although both synchronous computer-mediated and face-to-face interactions facilitate vocabulary acquisition, the 3 weeks delayed post-test shows a downward trend in the face-to-face group. In terms of negotiation of meaning, the synchronous computer-mediated environment produces slightly higher production compared to the face-to-face environment. The discourse features employed by the synchronous computer-mediated group were different from the face-to-face group during the negotiation of meaning. The findings in this study provide helpful insights for educators in terms of vocabulary teaching when designing the interactive tasks.